Effect of Diseases on Livestock Animals in Kahungye Sub-County Kabale District. - Tibasiima, Charity (Kabale University, 2024)
The study titled "Effect of Diseases on Livestock Animals in Kahungye Sub County, Kabale District" aimed to explore the causes, impacts, and potential solutions for livestock diseases. A survey research design was employed, incorporating interviews with farmers, veterinarians, and stakeholders in six purposively selected villages. Data were collected through questionnaires, focus group discussions, key informant interviews, and participant observation, supplemented by secondary data. The findings revealed that colic (38%) and pneumonia (25%) were the most prevalent diseases among livestock, while coccidiosis (5%) was the least reported. The effects included a 45% reduction in livestock productivity and increased veterinary costs, resulting in economic losses for farmers. Respondents suggested vaccination programs (80%), improved animal handling (65%), and biosecurity measures (50%) as key solutions to mitigate these diseases. Data analysis was conducted using SPSS and Microsoft Excel to generate frequencies and percentages. The study concluded that a combination of proper management practices and effective disease prevention strategies is essential to safeguard livestock health and productivity. It recommended strengthening veterinary services, promoting awareness campaigns on disease control, and enhancing government support for disease prevention initiatives.